An oscillatory pipelining mechanism supporting previewing during visual exploration and reading. Issue 12 (December 2021) - Jensen, Ole; Pan, Yali; Frisson, Steven; Wang, Lin
Abstract : Humans have a remarkable ability to efficiently explore visual scenes and text using eye movements. Humans typically make eye movements (saccades) every 250 ms. Since saccade initiation and execution take 100 ms, this leaves only 150 ms to recognize the fixated object (or word) while simultaneously previewing candidates for the next saccade goal. We propose a pipelining mechanism where serial processing occurs within a specific brain region, whereas parallel processing occurs across different brain regions. The mechanism is timed by alpha oscillations that coordinate the saccades, visual recognition, and previewing in the cortical hierarchy. Consequently, the neuronal mechanism supporting natural vision and saccades must be studied in unison to uncover the brain mechanisms supporting visual exploration and reading. Highlights: Humans have a remarkable ability to efficiently acquire information from natural scenes and text by means of saccadic exploration. Visual exploration is surprisingly efficient given the temporal and spatial constraints imposed by the visual system. As such, both information from current fixations as well as upcoming parafoveal locations must be processed within a 150-ms time window. We propose a novel mechanism in which visual exploration and reading are supported by a pipelining mechanism in which serial processing occurs within a specific brain region, whereas parallel processing occurs across different brain regions. The timing of the pipelining mechanism is organized by alpha oscillations. The pipelining mechanism predicts that fixated and parafoveal objects/words are represented at different phases of an alpha cycle. Consistent with the mechanism, data in humans and non-human primates point to a link between the timing of saccades and alpha oscillations.